Microwave assisted sintering of Na-β''-Al2O3 in single mode cavities: Insights in the use of 2450 MHz frequency and preliminary experiments at 5800 MHz. Issue 18 (15th December 2020) - Mortalò, Cecilia; Rosa, Roberto; Veronesi, Paolo; Fasolin, Stefano; Zin, Valentina; Deambrosis, Silvia Maria; Miorin, Enrico; Dimitrakis, Georgios; Fabrizio, Monica; Leonelli, Cristina
Abstract: Microwave assisted sintering of Na-β''-Al2 O3 in single mode cavities was accurately investigated. The use of single mode cavity allowed monitoring the parameters affecting the sintering process, like the forward power, together with the temperature evolution, making possible to perform energy efficiency and specific energy consumption evaluations. Experiments have been performed at the frequency of 2450 MHz, but preliminary results are also reported using the higher frequency of 5800 MHz, in order to investigate its effect on important parameters like the power density distribution as well as the penetration depth, which are responsible of the resulting heating rate and sintering outcome. Dielectric properties of the powders were measured as a function of temperature in order to partially predict and support the understanding of their experimental heating behaviour. Furthermore, dielectric properties provide the fundamental information needed for the multiphysics numerical simulation, performed with the aim to reach insights into the power density evolution in the specimen as sintering proceeds.